PROSES HUKUM TERHADAP PRESIDEN PUTIN ATAS DUGAAN KEJAHATAN PERANG DALAM AGRESI RUSIA KE UKRAINA - Uyan Wiryadi; Simanjuntak, Mangisi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The world was shocked by the issuance of an arrest warrant against Russian President Vladimir Putin by the International Criminal Court (ICC). The arrest warrant was issued on charges of war crimes in the form of the forced deportation of Ukrainian children during a special Russian military operation. The Kiev side reported that more than 16,000 children from Ukraine had been deported to Russia since the invasion began February 24, 2022. Many of them were allegedly placed in orphanages or adopted by Russian citizens. Furthermore, a warrant for Putin's arrest was issued a day after United Nations investigators condemned the forced transfer and deportation of Ukrainian children, seizing them from their parents, as war crimes. UN investigators said the parents of the "dispossessed" children disclosed that their children would later be placed in foster families or in orphanages under Russian rule. As head of state of Russia, Putin is held criminally responsible for war crimes committed by Russia against Ukraine. Specifically, deportation of minors. The Rome Statute of 1998 Article 8 paragraph (vii) states that the unlawful deportation or transfer of persons or unlawful confinement constitutes a war crime.